Study on Assimilation of Architecture in Fashion Wear - Baruah, Sabita; Patil, Namrata (New Approaches in Engineering Research Vol. 14, 2021)
Creativity in the field of fashion is known to draw inspiration from many unusual sources. One such source happens to be architectural styles of buildings that strive to preserve the cultural heritage of an entire civilization. The styles might not only inspire simple motifs and silhouette types, but also weave a story that will eventually find its way into more intricate forms of human clothing. Therefore, this paper will lead us to first understand the inner anatomy of a piece of architecture. Later, the paper will help us identify the finer elemental artifacts that can be retrieved and assembled into an exotic fashion creation. The final objective is to establish the hidden relationships, influences, similarities, and differences between the fields of architecture and fashion design. Within India, the great monuments whose architectures are waiting to be exploited for fashion ideas include the Golden Temple, Charminar, Meenakshi, Temple, and Hampi. This study reveals that many fashion designers have been inspired by intricate elements of architecture.